Oesophagectomy without thoracotomy in the treatment of oesophagic neoplasm - Piacenza, Guillermo; Bergalli, Luis; Carriquiry, Luis; Pradines, Jorge; Montandon, Pablo; Rocha, Osvaldo (Cirugía del Uruguay, 1984)
The oesophagectomy wlthout toracotomy technlque is discussed in connectlon wlth eight cases treated between 1979 and 1983. Cases treated and results are analyzed. Technique employed is descrlbed. lmportance is given to the indication of the procedu· re that constitutes an alternativa method. Mention is made of the utility of same In begnin pathology of oesophagus and malignant lesions of the hypopharinx. Finally, its advantages are examinad in connection with the thoracic and abdomlnal malignant pathology of the oesophagus, stresslng the palliative character of . the procedure .